Evaluation of the accuracy of renal depth estimation formulas in horseshoe kidney. Issue 49 (December 2017) - Ma, Guangyu; Chen, Yingmao; Shao, Mingzhe; Tian, Jiahe; Xu, Baixuan
Abstract : Abstract: Estimation formulas are usually used to calculate renal depth when glomerular filtration rate (GFR) is measured by the Gates method. Horseshoe kidney (HSK) anatomical structure is different from the normal form of the kidney. The existing formulas are based on the normal form. It is unknown whether the existing formulas are valid in HSK patients. This study was performed to estimate the accuracy of the existing 6 renal depth estimation formulas in HSK. Renal depth and total thickness (T, cm) of the body at the level of the kidneys were measured by CT in 94 HSK patients. Their sex, age, height (H, cm), and weight (W, kg) were recorded. The existing 6 estimation formulas were used to obtain estimated renal depth. Correlation coefficients, Bland-Altman analysis, and paired t test were performed between estimated and the CT measured renal depth. Estimated renal depths were all lower than the CT measured renal depths and there was significant difference between estimated and CT measured renal depth. The CT measured renal depth and estimated renal depth derived from Ma GY formula correlated best (right: r = 0.80, P < .01; left: r = 0.77, P < .01). The renal depth derived from Tonnesen formula was significantly lower than the CT measured renal depth. The agreement between the estimated renal depth derived from Tonnesen formula and the CT measured renal depth was the worst, with the mean difference of (right: −3.11 ± 1.13 cm; left: −2.79 ± 1.07 cm). The agreement between the estimated renal depth derived from Li Q formula and Ma GY formula and the CT measured renal depth was the best, with the mean difference of right: −1.68 ± 1.09 cm; left: −1.32 ± 1.06 cm and right: −1.59 ± 1.01 cm; left: −1.59 ± 0.99 cm, respectively. But the greatest error of the difference between Li Q formula and Ma GY formula estimated depth and the CT measured depth was up to −4.83 cm, and the estimated deviation is unacceptable. All the existing formulas do not fully apply to HSK. To provide reliable and accurate estimates of renal depth, we should develop a new formula to estimate the renal depth in HSK patients.